Angiosome study of the first digital feet space, for reconstruction of the digital tip - Ruiz Rodrigo, Banegas; Alejandro, Espejel Blancas José; Carlos Rubén, Baca Domínguez; Gerardo, Campos Angulo; Alejo Fuentes, Luis Jesús; Gómez Mendoza, Francisco Fabián; Espinoza Torres, Juan Pablo; Carazo Quiroz, Luis Rodrigo; Ramos Lojero, Víctor Manuel; Isaac, Valderrama Treviño Alan; Baltazar, Barrera Mera (International Journal of Research in Medical Sciences, 2019)
Background: The concept of angiosome explains the anatomical variations that exist between the vessels of different regions of the body and helps to understand the contributions of arterial blood supply to the skin and adjacent structures, dividing the human body into three-dimensional vascular blocks. Methods: This was an observational and descriptive study. In both lower extremities of 5 corpses with adequate tissue preservation in the operating room attached to the teaching area of the National Institute of Forensic Sciences in Mexico City. Angiosome study of the medial neurocutaneous flap of the second toe of both feet was performed. Results: The average, in centimeters, of the surface of the flaps was 1.57 cm x 2.47 cm, the average diameter of the inter-metatarsal digital artery was 1.1 millimeters and the average diameter of the veins draining the angiosome was 1.4 millimeters. The most constant anatomy was that of the nerve, which was present in all cases, with the digital nerve forming the neurosome of the flap. Conclusions: To obtain optimal results in microsurgery transfers, it is necessary to have a technique that is quick for harvesting the flap and with adequate systematization so as not to injure the neurovascular bundle, this is achieved through complete anatomical knowledge, without forgetting the main variants.